2010
DOI: 10.1016/j.paid.2009.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Need and Ability to Achieve Closure: Relationships with symptoms of psychopathology

Abstract: Recent literature has asserted that excessive choice in everyday life may pose a burden on mental health. The present research further qualifies this claim by focusing on the role of stable individual differences in Need for (cognitive) Closure (NFC) and Ability to Achieve Closure (AAC), which tap into the cognitive-motivational aspects of decision making and choice. The effects of these two distinct components of cognitive closure on mental health and symptoms of psychopathology were investigated in a non-cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
2
15
0
1
Order By: Relevance
“…Similarly, the correlation between the need for closure and intolerance to uncertainty in this study also seems to support this conclusion. There are studies in the literature that show that as the need for closure increases, the intolerance to uncertainty also increases (5,6,11,(18)(19). The result obtained in this study is also consistent with the literature, and this conformity seems to refer to the criterion-based validity of the scale.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, the correlation between the need for closure and intolerance to uncertainty in this study also seems to support this conclusion. There are studies in the literature that show that as the need for closure increases, the intolerance to uncertainty also increases (5,6,11,(18)(19). The result obtained in this study is also consistent with the literature, and this conformity seems to refer to the criterion-based validity of the scale.…”
Section: Discussionsupporting
confidence: 90%
“…Decision-making is defined as a complex set of steps in which the individual chooses, evaluates, and enforces one of these alternatives, and this is directly related to the need for cognitive closure (19). According to Bar-Tal (13), decision-making can be defined as an orientation to eliminate the distress that is experienced when there is more than one way to lead to a result that is thought to meet a need.…”
mentioning
confidence: 99%
“…Yet, interventions based on the reduction of people's AAC in order to curb the use of stereotypes when judging people may be more suitable for specific, acute situations, such as job interviews. Given the potentially negative "side effects" of low AACS on mental well-being mentioned earlier (see Roets & Soetens, 2010), it seems that long-lasting reduction of AAC should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Roets and Soetens (2010) showed that whereas closure needs were positively related to symptoms of psychopathology in a large nonclinical adult sample, the ability to achieve closure (measured by a combination of the original decisiveness scale and the AACS scale) showed strong negative relations with those symptoms. The authors proposed that in today's complex world, high NFC may lead to more distress in everyday life decision making (see , whereas low AAC may lead Roets and Van Hiel (2011b), based on the full revised NFC scale (Roets & Van Hiel, 2007), original scale by Webster and Kruglanski (1994).…”
Section: Need Versus Ability To Achieve Closurementioning
confidence: 99%
“…This aggregated sample comprised new samples as well as data from Dhont, Roets, and Van Hiel (in revision); Onraet, Van Hiel, Roets, and Cornelis (in press); Roets and Soetens (2010); and Roets and Van Hiel (2008;in press). The total sample consisted of 1142 adults and 442 students of which 36% were men.…”
Section: Participantsmentioning
confidence: 99%